Tears Analysis on Luxurious Hotel Endorsement Marketing Strategy - Lasmana, Douwes; Gunthoro, Enzie (Journal of Tourism and Creativity, 2022)
Along with the development of the internet that has been very advanced in the present era, the development of marketing in Indonesia has also evolved which we can see on some social media using certain parties such as endorsers or celebrity with this opportunity that many companies make them effective marketing tools in the present term, Endorsement, but in this discussion, we will further analyze the marketing endorsement strategy at Hotel X and more in finding out what is needed from an endorser to become an endorser suitable for five-star hotels by means of the TEARS model ( Trustworthiness, Expertise, Attractiveness, Respect, Similarity). The methodology used is descriptive qualitative with the method of collecting data in an unstructured interview where correspondents can answer freely and express all their opinions in detail so that the authors get more results and information. The results of this study indicate that the way the TEARS model is very supportive in the process of selecting Endorsers for five-star hotels